Impact of Clinical Pharmacists-driven Bundled Activities from Admission to Discharge on 90-day Hospital Readmissions and Emergency Department Visits - Bayan Muhannad Al Abd; Juhaina Salim Al-Maqbali; Ibrahim Al-Zakwani (Oman Medical Journal, 2023)
Objectives: Patient-centered clinical pharmacists’ activities play a major role in improving clinical outcomes by optimizing the efficacy of drug therapies and minimizing associated toxicities during hospitalization, at the transition of care, and upon discharge. We aimed to compare the impact of comprehensive versus partial clinical pharmacists-driven bundled of care services on the rate of 90-day hospital readmissions and emergency department (ED) visits. Methods: This retrospective study included all admitted patients who received a comprehensive or partial bundle of clinical pharmacy services (medication history, interventions, counseling, and discharge prescription review) from 1 January 2021 to 30 June 2021 at Sultan Qaboos University Hospital. The comprehensive bundle of care included the four services, while the partial bundle of care included one, two, or three services only. Analyses were performed using univariate and multivariate statistical techniques. Results: The study included 430 patients with a mean age of 56.0±21.0 years, and 43.7% (n = 188) were male. Of the patients, 12.1% (n = 52) received a comprehensive bundle of care. Compared with the partial bundle of care group, the comprehensive bundle of care group had significantly more patients with diabetes (65.4% vs. 42.9%; p =0.002), ≥ 3 comorbidities (50.0% vs. 29.4%; p =0.003), and polypharmacy (≥ 5 medications) (73.1% vs. 46.0%; p < 0.001). The comprehensive bundle of care group was significantly associated with a lower 90-day readmission rate (adjusted odds ratio (aOR) = 0.27, 95% CI: 0.90–0.82; p =0.021) but not with ED visits (aOR = 0.57, 95% CI: 0.13–2.57; p =0.461). Conclusions: This study demonstrated a significant reduction in the 90-day readmission rate for patients on a comprehensive bundle of care but not ED visits. These findings emphasize the importance of the comprehensive services provided by clinical pharmacists on the healthcare resources use and clinical outcomes.